An Giang University journal of science (An Giang University, 2017)
Contents CDIO an educational framework for curricular planning and outcome-based asessment; Comparative analysis on aucubin content in different ecotyes of plantain plant; Survey on prevalence of blood parasites on beef cattle in Cho Moi district - An Giang province;...